Evacuated Population in Stalingrad Region in 1941-1948 - V. V. Fedotov (Научный диалог)
Based on the archival materials, the article studies evacuation processes associated with the movement of the population that took place in the Stalingrad region in the period 1941-1948. The questions of asylum and accommodation of evacuated citizens as a special social group that existed during the Great Patriotic war are considered. The work reveals the labour activity, contribution of the evacuated population to the economy of the region, the mood of evacuees in the rear and their relationship with the indigenous population. The author assesses the activities of the authorities that led the movement and service of the evacuated population at different stages of the stay of refugees in the Stalingrad region. The author emphasizes that the additional sources of food sought in the field have greatly alleviated tensions in the food supply of refugees. It is noted that re-evacuation differed from evacuation in terms of timing, scale and other parameters. The scientific novelty of the research is seen in the fact that new materials discovered by the author in the archives are introduced into circulation. The study was conducted on materials of the State Archive of Volgograd region and the Centre of Documentation of the Newest History of the Volgograd region with the assistance of the scientific and statistical literature.